Perbandingan Hasil Belajar Mahasiswa Antara Metode OSCE dan Mini-CEX pada Asuhan Bayi Baru Lahir - R, Rahma Winahyi; Siduppa, Basuki Rahmat Masdi (Lembaga Penelitian dan Pengabdian Masyarakat Institut Ilmu Kesehatan Pelamonia, 2025)
Background: The evaluation of clinical competence among midwifery students requires objective and standardized methods to ensure mastery of clinical skills. Objective Structured Clinical Examination (OSCE) and Mini Clinical Evaluation Exercise (Mini-CEX) are two widely used assessment methods, each with different characteristics. Objective: This study aimed to analyze the differences in learning outcomes between OSCE and Mini-CEX methods in evaluating the clinical competence of midwifery students in neonatal care. Methods: This research employed a quasi-experimental design with a post-test only non-equivalent group approach. The sample consisted of 60 fourth-semester students divided into two groups, with 30 students evaluated using OSCE and 30 students evaluated using Mini-CEX. The research instrument was a validated clinical competency assessment checklist. Data were analyzed using an Independent Samples t-Test with a significance level of p<0.05. Results: The mean learning outcome score in the OSCE group was higher (85.2±5.6) compared to the Mini-CEX group (80.1±6.3), with p=0.001 indicating a significant difference. Conclusion: OSCE is more effective in improving learning outcomes of midwifery students in neonatal care compared to Mini-CEX. The complementary implementation of both methods can be considered as an alternative strategy for comprehensive evaluation.